Zinc Serum Maternal Levels as a Risk Factor for Preeclampsia - Abarham Martadiansyah; Peby Maulina; Putri Mirani; Tia Kaprianti; Theodorus (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background. Preeclampsia is defined as gestational hypertension and proteinuria which can be measured by the elevation of liver transaminases to twice normal concentration, and the symptoms of increased intracranial pressure such as dizziness, blurred vision, and seizures. Zinc is an essential mineral for many biological functions and one of the trace elements that is directly involved in the oxidative/antioxidant balance, a pathogenesis process in preeclampsia that is highly dependent on dietary habits and supplements. This study was aimed to assess the association between serum zinc level with preeclampsia (PE). Methods: This observational, case-control study was performed on 90 women with singleton pregnancies at 28 to 42 weeks of gestation which were referred to the Department of Obstetrics and Gynecology, Dr. Mohammad Hoesin General Hospital, Palembang, between August 2020 to November 2020. 30 pregnant women with PE were selected as cases and 60 healthy pregnant women were selected as controls. Maternal serum zinc samples were collected. The collected data were entered into the master table. Tabulation, coding, and statistical data analysis were performed using SPSS version 20.0 for Windows. Results: The mean serum zinc levels in the case group and control group were 43,90 ± 15,79 µg/dL (ranged from 15 to 86 µg/dL) and 48,77 ± 10,54 µg/dL (ranged from 22 to 83 µg/dL), respectively. A value of serum zinc levels with the best sensitivity and specificity was 45,5 µg/dL. Conclusion: There was a significant association between maternal serum zinc level with PE. The risk of PE was 3,2 times higher in pregnant women with serum zinc levels of ≤45,5 mcg/dL compared to pregnant women with serum zinc levels of >45,5 mcg/dL. In this case it is necessary to supplement zinc earlier in pregnancy to reduce the risk of preeclampsia.